Association Between Smoking and p53 Mutation in Oesophageal Squamous Cell Carcinoma: A Meta-analysis. Issue 6 (June 2015) - Wu, X.C.; Zheng, Y.F.; Tang, M.; Li, X.F.; Zeng, R.; Zhang, J.R.
Abstract Aims Several studies have evaluated the association between smoking and p53 mutation in oesophageal squamous cell carcinoma (ESCC), but the conclusions are inconsistent. The aim of the present study was to carry out a meta-analysis evaluating the relationship between smoking and p53 mutation in patients with ESCC. Materials and methods Eligible studies were identified through searches in PubMed and EMBASE. The odds ratio with 95% confidence interval was used to assess the association. In total, 20 studies were identified that met the selection criteria; these studies were analysed using STATA 12.0 software. Results The 20 studies identified comprised 1524 ESCC patients, of whom 72.97% were smokers and 27.03% were non-smokers. The pooled odds ratio of p53 mutation in ESCC for any cigarette smoking versus no smoking was 1.28 (95% confidence interval = 0.88–1.88). The estimated odds ratios were 1.06 (95% confidence interval = 0.56–2.00, based on five studies, 129 light smokers and 70 non-smokers) for light smoking and 2.01 (95% confidence interval = 1.12–3.60, based on five studies, 223 heavy smokers and 73 non-smokers) for heavy smoking. Conclusion The results of our meta-analysis indicate an overall positive relationship between heavy smoking and p53 mutation in ESCC. Heavy smokers with ESCC have a higher risk for p53 mutation than non-smokers. Large-scale clinical studies are still needed to draw a more precise conclusion.